The limitations of formalism - Unikauskas, Giedrius (Respectus Philologicus, 1999)
This article is another attempt to define the scope of literature, to consider methods and achievements in literary scholarship, and to weight theoretical alternatives. Literary creation is understood here as a complex of form and content, and the opinion here expressed is that that formal analysis alone is an inadequate approach to questions of literary meaning.